Mechanically induced M2 macrophages are involved in bone remodeling of the midpalatal suture during palatal expansion - Lan Li; Mingrui Zhai; Chen Cheng; Shuyue Cui; Jixiao Wang; Zijie Zhang; Jiani Liu; Fulan Wei (SpringerOpen, 2024)
Abstract Background Palatal expansion is a common way of treating maxillary transverse deficiency. Under mechanical force, the midpalatal suture is expanded, causing local immune responses. This study aimed to determine whether macrophages participate in bone remodeling of the midpalatal suture during palatal expansion and the effects on bone remodeling. Methods Palatal expansion model and macrophage depletion model were established. Micro-CT, histological staining, and immunohistochemical staining were used to investigate the changes in the number and phenotype of macrophages during palatal expansion as well as the effects on bone remodeling of the midpalatal suture. Additionally, the effect of mechanically induced M2 macrophages on palatal osteoblasts was also elucidated in vitro. Results The number of macrophages increased significantly and polarized toward M2 phenotype with the increase of the expansion time, which was consistent with the trend of bone remodeling. After macrophage depletion, the function of osteoblasts and bone formation at the midpalatal suture were impaired during palatal expansion. In vitro, conditioned medium derived from M2 macrophages facilitated osteogenic differentiation of osteoblasts and decreased the RANKL/OPG ratio. Conclusions Macrophages through polarizing toward M2 phenotype participated in midpalatal suture bone remodeling during palatal expansion, which may provide a new idea for promoting bone remodeling from the perspective of regulating macrophage polarization.